PENGARUH KEPEMIMPINAN IKLIM ORGANISASI MOTIVASI PADA KINERJA KARYAWAN PT DELTA SUKSES MAKMUR - Palupi, Dyah Ayu Puri; Lyna, Lyna (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The formulation of the problem in this study is to analyze the influence of organizational climate, leadership, motivation on employee performance at PT Delta Merlin Dunia Textile VII. The population in this study were all employees of PT Delta Sukses Makmur totaling 30 staff. In this study using a saturated sample, which is a sampling technique when all members of the population are used as samples. The analytical method in this study uses instrument testing, classical assumption test, multiple linear analysis, t-test, F test, and R2 test. The results of the study on multiple linear regression analysis showed that leadership and motivation variables had a positive and significant effect on employee performance, while organizational climate had a positive but not significant effect on employee performance at PT Delta Sukses Makmur. The results of the Adjusted R Square coefficient of determination obtained the Adjusted R Square coefficient of determination the Adjusted R Square coefficient of determination of 0.979 means it is known that the influence given by leadership, organizational climate, motivation on employee performance is 97.9% while the remaining 2.1% is influenced by other variables not included in this study, such as compensation, work environment, discipline